A note on “Study on multi-objective linear fractional programming problem involving pentagonal intuitionistic fuzzy number” - Hassanpour, Hassan; Tayyebi, Javad (Results in control and optimization, 2025)
This note presents a critical assessment of the paper authored by Sahoo et al. (2022) titled “Study on multi-objective linear fractional programming problem involving pentagonal intuitionistic fuzzy number” published in Results in Control and Optimization, volume 6, 100091. The note highlights a notable shortcoming in the equivalence between two optimization problems, which leads to two incorrect results, containing two theorems and the proposed method for solving intuitionistic fuzzy multi-objective linear fractional optimization problems.